Analysis of Translation Method of the Idiomatic Phrases in J.K. Rowling's Novel “Harry Potter and the Deathly Hallows” - Beatrice Stephanie; Muhammad Zaki Pahrul Hadi (CV Insan Kreasi Media, 2024)
Among works of fiction, idiomatic phrases are some of the most complicated problems in translation. Idioms are a significant part of every language whose metaphorical meanings cannot be directly conveyed through translation. The idioms help maintain most of the subtlety and unique cultural characteristics that define a language. This paper will elaborate on the translation of idiomatic phrases in the novel